Relationship of Dental Caries with Quality of Life in Early Childhood at Baiturrohim PAUD, Palembang City - Nur Azizah; Ismalayani Ismalayani; Dhandi Wijaya (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2021)
Quality of life is a person's ability to enjoy normal life activities. Healthy living is part of the quality of life, because it is healthy not only physically but also mentally and socially healthy. Oral health is an inseparable part of general health because dental and oral health conditions can affect daily life. This study aims to determine the relationship between dental caries and quality of life in early childhood. This cross sectional study conducted in February 2021 at PAUD Baiturrohim, Palembang. The subject consisted of 67 children taken by simple random sampling. Dental caries status was measured using the def-t index and children's quality of life was measured using the Early Childhood Oral Health Impact Scale (ECOHIS). Data were analyzed using the Chi-Square test with a 95% confidence interval. The def-t index category in early childhood in Baiturrohim PAUD with very high criteria was 56.7%, high criteria was 16.4%, moderate and low criateria were 10.4% respectively and very low criteria was 6%. The quality of life in early childhood in Baiturrohim PAUD with bad criteria was 53.7%, moderate criteria was 25.4%, and good criteria was 25.4%. It was found that there is a significant relationship between the incidence of dental caries and quality of life (p0.05).